2023
DOI: 10.3390/antibiotics12111569
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of AMR Risks Arising as a Consequence of Using Biocides and Certain Metals in Food Animal Production

Christian James,
Stephen J. James,
Bukola A. Onarinde
et al.

Abstract: The focus of this review was to assess what evidence exists on whether, and to what extent, the use of biocides (disinfectants and sanitizers) and certain metals (used in feed and other uses) in animal production (both land and aquatic) leads to the development and spread of AMR within the food chain. A comprehensive literature search identified 3434 publications, which after screening were reduced to 154 relevant publications from which some data were extracted to address the focus of the review. The review h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 185 publications
0
2
0
Order By: Relevance
“…Such genetic linkage between metal- and antibiotic-resistance traits has been reported on plasmids in Enterobacteriaceae and in other bacteria isolated from other animal feces, soil, or sewage (4750). It has been shown that metals used in animal feed accumulate and persist in food animals, and may impact the development of AMR in primary animal and food production environments (51). Many studies indicate that the spread of AMR introduced through the application of manure to agricultural fields leads to its further spread within the food chain, and may pose a risk to human health (17, 5254).…”
Section: Discussionmentioning
confidence: 99%
“…Such genetic linkage between metal- and antibiotic-resistance traits has been reported on plasmids in Enterobacteriaceae and in other bacteria isolated from other animal feces, soil, or sewage (4750). It has been shown that metals used in animal feed accumulate and persist in food animals, and may impact the development of AMR in primary animal and food production environments (51). Many studies indicate that the spread of AMR introduced through the application of manure to agricultural fields leads to its further spread within the food chain, and may pose a risk to human health (17, 5254).…”
Section: Discussionmentioning
confidence: 99%
“…Such genetic linkage between metal-and antibioticresistance traits has been reported on plasmids in Enterobacteriaceae and in other bacteria isolated from other animal feces, soil, or sewage(Summers et al 1993;Ghosh et al 2000;Hasman and Aarestrup 2002;Rozwandowicz et al 2018). It has been shown that metals used in animal feed accumulate and persist in food animals, and may impact the development of AMR in primary animal and food production environments(James et al 2023). Many studies indicate that the spread of AMR introduced through the application of manure to agricultural elds leads to its further spread within the food chain, and may pose a risk to human health(Do et al 2022ażejewska et al 2022Zalewska et al 2023Zalewska et al , 2024.…”
mentioning
confidence: 99%